2017
DOI: 10.1186/s12873-017-0133-6
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and treatment of severe sepsis in the emergency department: retrospective study in two French teaching hospitals

Abstract: BackgroundSepsis management in the Emergency Department remains a daily challenge. The Surviving Sepsis Campaign (SSC) has released three-hour bundle. The implementation of these bundles in European Emergency Departments remains poorly described.The main objective was to assess the compliance with the Severe Sepsis Campaign 3-h bundle (blood culture, lactate dosage, first dose of antibiotics and 30 ml/kg fluid challenge). Secondary objectives were the analysis of the delay of severe sepsis recognition and desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Most studies have reported non-patient related factors as barriers. Improper diagnosis of sepsis such as underestimating the severity of sepsis, difficulty and delay in recognising sepsis, and clinical reliance on development of hypotension to begin treatment have been repeatedly reported [ 32 , 34 , 38 ]. Experience of the treating healthcare professional has been identified as an inhibiting factor when inexperienced junior physicians and those without emergency training care for patients during the initial hours [ 30 , 31 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies have reported non-patient related factors as barriers. Improper diagnosis of sepsis such as underestimating the severity of sepsis, difficulty and delay in recognising sepsis, and clinical reliance on development of hypotension to begin treatment have been repeatedly reported [ 32 , 34 , 38 ]. Experience of the treating healthcare professional has been identified as an inhibiting factor when inexperienced junior physicians and those without emergency training care for patients during the initial hours [ 30 , 31 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Morr et al, report that correctness of the classification of sepsis and its severity had no impact on early initiation of fluid bolus [ 37 ]. Three studies have reported that overcrowding in the emergency department and its associated factors such as increased occupancy rate, increased patient hours and patients presenting between 0700 and 1900 h was strongly associated with delays in initiating fluid bolus [ 36 , 38 , 61 ]. However, the retrospective study by Kang et al, shows that over-crowding had no impact on the compliance rate [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, patients may represent subgroups that could benefit from targeted interventions, if they have increased expression of genes associated with the adaptive and innate immune system, or alternatively, higher expression in specific coagulopathic pathways [42][43][44][45][46]. Other applications for host response transcription assays could be the identification of causative pathogens or prognostication of sepsis [42,[47][48][49][50][51][52]. However, in the present review we will focus exclusively on the diagnosis of infection in critically ill patients.…”
Section: Biomarker Discovery Using a Transcriptomics Approachmentioning
confidence: 99%